Madness Concept in Rusdi Mathari's Novel: A Foucauldian Reading of Merasa Pintar, Bodoh Saja Tak Punya - Indriyani, Jiphie Gilia; An Adzhani, Shabrina; Shofah, Novia Adibatus (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study of the literary work Merasa Pintar, Bodoh Saja Tak Punya by Rusdi Mathari employs Michel Foucault’s theory of madness to analyze narrative data and identify the concept of madness within the epistémè of the village community where the main character, Cak Dlahom, resides. The main character gets different treatment from two groups of people he meets in his daily life. The first group is people who always need confirmation from Cak Dlahom. The second group consists of people who make a priori judgments, attribute the concept of madness to Cak Dlahom, treat him as a different person, and then laugh at and ignore him. However, Cak Dlahom managed to fight the social epistémè by creating a narrative that broke the stigma. This research successfully identifies the patterns and impacts of societal judgment on individuals who are perceived as different. Additionally, there is an image of an individual’s ability to resist the dominant view and shape their own narrative in society.